The effect of adversity on process innovations and managerial incentives - Benoît Dostie; Rajshri Jayaraman (Center for Economic Studies and ifo Institute (CESifo), 2009)
This paper asks whether adversity spurs the introduction of process innovations and increases the use of managerial incentives by firms. Using a large panel data set of workplaces in Canada, our identification strategy relies on exogenous variation in adversity arising from increased border security along the 49th parallel following 9/11. Our longitudinal difference-in-differences estimates indicate that firms responded to adversity by introducing new or improved processes, but did not change their use of managerial incentives. These results suggest that the threat of bankruptcy may provide impetus for improving efficiency.
Keywords: L20; O31; M52; J33; 330; Krisenmanagement; Innovation; Führungskräfte; Leistungsorientierte Vergütung; Leistungsmotivation; Theorie; Kanada